2012
DOI: 10.1099/jmm.0.039511-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of monoclonal antibodies to recombinant terrelysin and characterization of expression in Aspergillus terreus

Abstract: Aspergillus terreus is an emerging pathogen that mostly affects immunocompromised patients, causing infections that are often difficult to manage therapeutically. Current diagnostic strategies are limited to the detection of fungal growth using radiological methods or biopsy, which often does not enable species-specific identification. There is thus a critical need for diagnostic techniques to enable early and specific identification of the causative agent. In this study, we describe monoclonal antibodies (mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Current knowledge suggests that hemolysins are pore-forming toxins that interact with specific ligands on the surface of various target cells [1]. Although extensively studied in various bacterial species [1,2], hemolysins have also been reported in fungi [3,4], plants [5], invertebrates [68], and mammals (perforins) [9]. Bacterial hemolysins have been well characterized due to the role of these proteins in pathogenesis and, their structural details, mechanisms of hemolysis, ligand differences on target cells, and diagnostic potential have been described [2,10– 19].…”
Section: Introductionmentioning
confidence: 99%
“…Current knowledge suggests that hemolysins are pore-forming toxins that interact with specific ligands on the surface of various target cells [1]. Although extensively studied in various bacterial species [1,2], hemolysins have also been reported in fungi [3,4], plants [5], invertebrates [68], and mammals (perforins) [9]. Bacterial hemolysins have been well characterized due to the role of these proteins in pathogenesis and, their structural details, mechanisms of hemolysis, ligand differences on target cells, and diagnostic potential have been described [2,10– 19].…”
Section: Introductionmentioning
confidence: 99%
“…(42) Targeting a highly expressed protein such as enolase was hypothesized to result in improved immunoassay sensitivity compared to other fungal antigens, such as terrelysin that may only be expressed during a specific growth stage of a fungal species. (21) Although the production of the IgG 1 isotype MAb 1C7 is an exciting development for the detection of C. globosum and other members of Sordariomycetes, the results of these preliminary immunoassay studies demonstrated that MAb 1C7…”
Section: Resultsmentioning
confidence: 99%
“…Fusion of splenocytes with SP2/ 0-AG14 myeloma cells (ATCC# CRL-1581) was performed as previously described. (21,22) Hybridomas were selected by growing cells in Dulbecco's Modified Eagle Medium (DMEM, Life Technologies, Rockville, MD) supplemented with 1 mM sodium pyruvate, 100 U/mL penicillin, 100 mg/mL streptomycin, 0.292 mg/mL L-glutamine, 100 mM sodium hypoxanthine, 16 mM thymidine, 10% fetal calf serum (FCS, HyClone, Logan, UT), and 100 U/mL IL-6 (Boerhinger, Mannheim, Germany). DMEM was also supplemented with azaserine for selective propagation of hybridomas.…”
Section: Splenocyte Fusion and Hybridoma Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion of splenocytes with SP2/0-AG14 myeloma cells was performed as previously described, (1,2) and hybridoma cells were cultivated in Dulbecco's Modified Eagle Medium. The supernatant fluid from confluent hybridomas was diluted 1:2 (v/v) in PBS 0.05% Tween-20 containing 3% non-fat dry skim milk powder and tested using a recombinant C. globosum enolase indirect ELISA.…”
mentioning
confidence: 99%